Determinants of Personal Financial Distress: Testing the Interaction Effect of Financial Self-efficacy - Angelica, Cinthia; Heriyadi; Wendy; Giriati; Mustaruddin (Yayasan Sinergi Kawula Muda, 2025)
Several students face financial distress that impacts their performance, mental health, academic progress, and difficulty achieving their financial obligations. Some factors, such as differential needs, cause females to have higher levels of personal financial distress than males. Financial Literacy affects the level of personal financial distress among undergraduate students. Lack of financial Literacy, uncertain income, and excessive anxiety can cause some mistakes in making financial decisions and end up with personal financial distress. This study aims to ascertain correlation between gender, income, anxiety, financial literacy and personal financial distress, and examines the moderating effect of financial self-efficacy. This study using quantitative research methodology, the data was tested using SPSS software. The findings of this study indicate that low income, anxiety, and financial literacy significantly affect personal financial distress. financial self-efficacy only moderates the relationship between financial literacy and personal financial distress. Undergraduate students with high financial literacy supported with high financial self-efficacy can reduce their risk of experiencing personal financial distress. Educational institutions can use these findings to design financial education programs to improve student welfare. This study is limited by the sample may not represent the wider population. For future researchers are recommended to using a larger scope of respondents and more predictors.